PEMBERDAYAAN MASYARAKAT PETANI MELALUI PROGRAM GABUNGAN KELOMPOK TANI DI DESA ADOW KECAMATAN PINOLOSIAN TENGAH KABUPATEN BOLAANG MONGONDOW SELATAN - KAMUNTUAN, DEIVI; POSUMAH, JOHNNY HANNY; TAMPI, GUSTAAF BUDDY (JURNAL ADMINISTRASI PUBLIK, 2019)
This research is titled the empowerment of farming communitiesthrough a joint farmer group (Gapoktan) program in the village of Adow,Pinolosian Sub-district, South Bolaang Mongong District. This type of researchuses qualitative research, the research informants are Gapoktan 1 person, 1person Gapoktan Chairperson, 15 Gapoktan Members, 1 Gapoktan Farmer 1person, 1 Person Village apparatus, data collection techniques using Interview,Observation, Documentation. Data analysis techniques using qualitativedescriptive analysis research, the focus of this study using the theory according toTotok and Poerwok. the results of this study are the programs implemented by theAdow Village Gapoktan that have supported farmers in their efforts to achieve abetter life. The Adow Village Gapoktan program has also been running well,those who play an active role in the program are those farmers who needempowerment.Keywords : Community; Empowerment. Farmers.